2011
DOI: 10.1089/vbz.2010.0093
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Human Hantavirus Infection and Zoonotic Investigation of Hantavirus Prevalence in Rodents in Western Java, Indonesia

Abstract: During febrile surveillance in the western Java City of Bandung, Indonesia, a patient with clinical symptoms consistent with hantavirus infection was found to have elevated titers of hantavirus-specific immunoglobulin M (IgM) and IgG antibodies. A subsequent epizoological investigation demonstrated a higher prevalence of hantavirus IgG antibodies in rodents trapped in the vicinity of the patient's home compared with rodents from a control area (13.2% vs. 4.7%, p = 0.036). The Old World Seoul hantavirus was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
3
13
0
1
Order By: Relevance
“…Moreover, rats have also been known as a carrier for several potential diseases transmitted to human being which affect their health. It has been reported that some rodents show their role as a vector for several zoonoses [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some endoparasites inhabiting their digestive organ were also identified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rats have also been known as a carrier for several potential diseases transmitted to human being which affect their health. It has been reported that some rodents show their role as a vector for several zoonoses [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Some endoparasites inhabiting their digestive organ were also identified.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement and support from the family are associated with a better physical and psychological adjustment (Li et al, 2013;Sumintardja et al, 2009). Family support is associated with a more positive effect, lower negative effect, reduced risk, enhanced health-related behaviours, better medical service utilization, and better illness management strategies, including higher rates of medication adherence in HIV patients (Broadhead et al, 2002;Carrieri et al, 2003;Kosasih et al, 2011;Latkin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A novel hantavirus designated as a Serang virus (SERV) was detected from R. tanezumi in Serang district of Banten Province by genetic examination [15]. These findings suggest that a variety of hantaviruses exist in Indonesia and may cause human diseases [6,10]. However, the prevalence of those viruses and the actual risk to human health remain unclear.…”
mentioning
confidence: 96%